Changes in intra-abdominal pressure and spontaneous breath volume by magnitude of lifting effort: highly trained athletes versus healthy men - Kawabata, M.; Shima, N.; Hamada, H.; Nakamura, I.; Nishizono, H. (European Journal of Applied Physiology, 2010)
Intra-abdominal pressure (IAP) is closely related to breathing behavior during lifting. Abdominal muscles contribute to both IAP development and respiratory function. The purpose of this study was to examine whether spontaneous breath volume and IAP altered with increased isometric lifting effort, and to compare the effect of different abdominal muscle strengths on these parameters. Maximal IAP during the Valsalva maneuver (maxIAP) and maximal isometric trunk flexor strength were measured in 10 highly trained judo athletes (trained) and 11 healthy men (controls). They performed isometric lifting with 0 (rest), 30, 45, 60, 75, 90, and 100% of maximal lifting effort (MLE). Natural inspiratory and expiratory volumes were calculated from air-flow data immediately before and after the start of lifting. IAP, measured using an intra-rectal pressure transducer during lifting, was normalized by maxIAP (%maxIAP). Trained athletes had higher maxIAP and stronger trunk flexor muscles than controls. A significant main effect of lifting effort was found on %maxIAP and respiratory volume. An interaction (lifting effort by group) was found only for %maxIAP. No significant group main effect or interaction was found for respiratory volume. Inspiratory volume increased significantly from tidal volume to above 60 and 45% of MLE in trained athletes and controls, respectively. Expiratory volume decreased significantly from tidal volume at above 30% of MLE in both the groups. These results suggest that spontaneous breath volume and IAP development are coupled with increased lifting effort, and strong abdominal muscles can modify IAP development and inspiratory behavior during lifting.